Incidental Finding and Management of Intralobar Sequestration of the Lung in A 24-Year-Old Man - Dhanjit Litt; Sumeet Gandhi; Sacha Bhinder; Maurice Blitz; Kieran McIntyre (Canadian Respiratory Journal)
Pulmonary sequestration is described as a dysplastic mass of lung tissue that lacks communication with the tracheobronchial tree and receives systemic rather than pulmonary arterial blood supply. Two distinct classifications, intralobar and extralobar, have been described. The present article discusses the etiology, clinical and radiographic features of pulmonary sequestration as well as the management of this condition when it is discovered incidentally.